Collective Total Synthesis of Aspidofractinine Alkaloids through the Development of a Bischler–Napieralski/Semipinacol Rearrangement Reaction - Wang, Shuang‐Hu; Si, Rui‐Qi; Zhuang, Qing‐Bo; Guo, Xiang; Ke, Tian; Zhang, Xiao‐Ming; Zhang, Fu‐Min; Tu, Yong‐Qiang (Angewandte Chemie International Edition, 2020)
A tandem Bischler–Napieralski/semipinacol rearrangement reaction has been developed for the purpose of assembling a bis(spirocyclic) indole framework, a privileged structural unit of aspidofractinine‐type monoterpenoid indole alkaloids, and was used in combination with a subsequent Mannich reaction to expeditiously construct the central bridged bicyclo[2.2.1]heptane ring system of these molecules with contiguous quaternary centers. The development of this novel strategy culminated in the collective total synthesis of four aspidofractinine alkaloids. A tandem Bischler–Napieralski reaction and semipinacol rearrangement was combined with a subsequent Mannich reaction for the expeditious construction of the bicyclo[2.2.1]heptanone motif of four aspidofractinine alkaloids (see scheme). The strategy further highlights the synthetic potential of tandem semipinacol rearrangement reactions in assembling spirocyclic ring systems with a congested chemical environment.